The Mansurovo Formation of the West Magnitogorsk Zone in the Southern Urals: Stratigraphy, Composition and Sedimentary Environments - A. M. Fazliakhmetov; O. Ju. Melnichuk; V. F. Juldashbaeva (Georesursy, 2025)
Research subject. Mansurovo formation (the (?)Silurian–Lower Devonian) in the Western Magnitogorsk zone of the Southern Urals, outcropped in the same-name village vicinity.   Aim. Clarification of the stratigraphy of the Mansurovo formation, detailing the composition and genesis of the litho- and volcaniclastic greywackes.   Materials and methods. The geochemical and petrographic composition of the Lower and Middle Devonian sediments in the North of the West Magnitogorsk zone was studied using 122 samples analyzed by ICP-MS and XRF methods. Of these, 50 samples are greywackes of the Mansurovo formations. The composition of the provenance and the sedimentary environments of greywackes were studied based on the ratio of minor and major elements and the description of thin sections. Features of stratigraphy are considered on the basis of published and stock biostratigraphic data and a comparative analysis of the geochemical composition of greywackes.   Results. The paleontological data accumulated to date are insufficient for confident dating of the Mansurovo Formation. Its age is conventionally assumed to be Silurian–Early Devonian. The ratios of minor elements in greywackes indicate the predominance of volcanogenic rocks of intermediate and basic composition in the provenance, which have geochemical characteristics of the formations of oceanic island arcs. The grain in graywackes is dominated by plagioclase and pyroxene porphyrites, crystalloclastics of pyroxenes and plagioclases. Of subordinate importance are grains of acidic volcanics, limestones, flints and siliceous-clayey rocks, microquartzites. The greywackes of the Mansurovo formation have a consistent composition and differ markedly in the ratio of certain elements from the tephrogenic rocks of the Irendyk formation, the Uskul formation and the greywackes of some sections of the Iltibanovo formation.   Conclusions. The Mansurovo formation is an independent stratigraphic unit and cannot be combined with the Irendyk formation. A detailed clarification of the age of the Mansurov strata is required. Only after this can it be used as a standard for comparing and linking tectonically separated blocks of the Lower Devonian and (?)Silurian deposits.